Formation of the innovative project financing model in modern conditions - Качурінер, Вікторія Львівна; Качурінер, В. Л.; Качуринер, Виктория Львовна; Kachuriner, Viktoriia L.; Грушко, Мальвіна Валеріївна; Грушко, М. В.; Грушко, Мальвина Валерьевна; Hrushko, Malvina V. (Baltija Publishing, 2019)
The state of development of the leading countries of the world proves that its main factors are innovative high technologies, new equipment, a new organization of labour and production, a new motivation for entrepreneurship. They ensure the economic stability of micro and macro systems, their competitiveness both in the domestic and foreign markets. Given the limited nature of state financial resources, the problem of finding additional sources of financing for the purpose of activating the development of innovation activity in Ukraine is becoming increasingly urgent. Today, many countries are actively implementing modern models of financing of innovative projects. In many countries, hybrid financial instruments are transformed in the modern environment into hybrid investment models such as crowdfunding and crowdinvesting. Research of existing models of innovative economic development is always relevant, development tendencies are constantly changing under the influence of global conditions. In Ukraine, it is possible to predict the development of such innovative models as: a resource model without high-tech production (natural resources – production – money); innovative model (transformation of money for research into knowledge – transformation of knowledge into skills of workers and innovations – transformation of innovations into goods – money); intellectual-donor model. An analysis of the world experience of using such forms of activation of innovation activity in the USA, Japan, Western Europe, the CIS, and other countries proves their relevance and prospects for Ukraine. At the same time, the efficiency of the functioning of innovation centres is largely determined by the proper level of financing of their activities, especially at an early stage. The model “university – innovation centres” aims to overcome the gap between education and the implementation of the knowledge gained in creating innovation. Within the framework of this model, two blocks are key: a block of joint research centres “university – industry” and a block of the creation of innovation centres and startup. The advantages of such a mechanism are: firstly, for business – direct state support for innovations, the possibility of investing under the state guarantees; and secondly, for the state – reduction of budgetary expenditures at the expense of funds attracted in the sphere of innovation activity, increase of innovation activity of priority sectors of the economy, distribution of innovative risks. The model of joint research centres “university – business structure” provides two variants of financing of such centres. The first option is based on the formation of a research centre in the form of corporation, which may include universities, private investors, local authorities, other sponsors and stakeholders. Traditionally, Ukraine has significant potential in some important fields of science, such as medicine, physics, astronomy, biology, chemistry, materials science, space science, and Earth science. Participation in Horizon 2020 allows creating additional opportunities for the successful development of these branches of science.

Стан розвитку провідних країн світу доводить, що його основними чинниками є інноваційні високі технології, нове обладнання, нова організація праці та виробництва, нова мотивація до підприємництва. Вони забезпечують економічну стійкість мікро- та макросистем, їх конкурентоспроможність як на внутрішньому, так і на зовнішньому ринках. Враховуючи обмеженість державних фінансових ресурсів, все більш актуальною стає проблема пошуку додаткових джерел фінансування з метою активізації розвитку інноваційної діяльності в Україні. Сьогодні багато країн активно впроваджують сучасні моделі фінансування інноваційних проектів. У багатьох країнах гібридні фінансові інструменти трансформуються в сучасному середовищі в гібридні моделі інвестування, такі як краудфандинг і краудінвестинг. Дослідження існуючих моделей інноваційного розвитку економіки завжди актуальні, тенденції розвитку постійно змінюються під впливом глобальних умов. В Україні можна передбачити розвиток таких інноваційних моделей, як: ресурсна модель без високотехнологічного виробництва (природні ресурси – виробництво – гроші); інноваційна модель (перетворення грошей на дослідження в знання – перетворення знань у навички працівників та інновації – перетворення інновацій на товари – гроші); інтелектуально-донорська модель. Аналіз світового досвіду використання таких форм активізації інноваційної діяльності в США, Японії, Західній Європі, СНД та інших країнах доводить їх актуальність та перспективність для України. При цьому ефективність функціонування інноваційних центрів значною мірою визначається належним рівнем фінансування їх діяльності, особливо на ранній стадії. Модель «університет – інноваційні центри» спрямована на подолання розриву між освітою та впровадженням знань, отриманих у створенні інновацій. У рамках цієї моделі ключовими є два блоки: блок спільних дослідницьких центрів «університет – промисловість» і блок створення інноваційних центрів і стартапів. Перевагами такого механізму є: по-перше, для бізнесу – пряма державна підтримка інновацій, можливість інвестування під державні гарантії; по-друге, для держави – зменшення бюджетних видатків за рахунок коштів, залучених у сферу інноваційної діяльності, підвищення інноваційної активності пріоритетних галузей економіки, розподіл інноваційних ризиків. Модель спільних наукових центрів «університет – бізнес-структура» передбачає два варіанти фінансування таких центрів. Перший варіант заснований на формуванні дослідницького центру у формі корпорації, до складу якої можуть входити університети, приватні інвестори, місцеві органи влади, інші спонсори та зацікавлені сторони. Традиційно Україна має значний потенціал у деяких важливих галузях науки, таких як медицина, фізика, астрономія, біологія, хімія, матеріалознавство, космічна наука, наука про Землю. Участь у Horizon 2020 дозволяє створити додаткові можливості для успішного розвитку цих галузей науки.
Kachuriner V. Formation of the innovative project financing model in modern conditions / V. Kachuriner, M. Hrushko // Baltic Journal of Economic Studies. - Vol. 5. - Issue 2. - Baltija Publishing, 2019. - Р. 65-72.
Keywords: innovative model; innovation centre; innovative project; financing mechanism; Horizon 2020; інноваційна модель; інноваційний центр; інноваційний проект; механізм фінансування; Горизонт 2020; Research Subject Categories::SOCIAL SCIENCES::Business and economics